2013
DOI: 10.3348/kjr.2013.14.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Shunt for the Treatment of Transjugular Intrahepatic Portosystemic Shunt Dysfunction

Abstract: ObjectiveTo investigate the safety, efficacy and long-term patency of parallel shunts (PS) in the management of the transjugular intrahepatic portosystemic shunt (TIPS) dysfunction.Materials and MethodsBetween March 2007 and October 2010, 18 patients (13 men and 5 women) who underwent TIPS revision with the creation of PS were evaluated retrospectively. In the first 10 patients, a 10-mm-diameter Wallgraft endoprosthesis was deployed; in the latter 8 patients, an 8-mm-diameter Fluency endoprosthesis was deploye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition to the studies mentioned above, literature on PS is rather limited. More recently, one group reported 18 out of 132 TIPS patients underwent PS placement after primary TIPS stent dysfunction, indicating that shunt patency of 1-year post-PS was higher in the patients who received Fluency ® endoprosthesis than those who received Wallgraft ® (87.5% vs 70.0%, P = 0.358)[29]. Another study described the application of PS in 10 cases of cirrhotic patients due to hepatitis B infection[30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the studies mentioned above, literature on PS is rather limited. More recently, one group reported 18 out of 132 TIPS patients underwent PS placement after primary TIPS stent dysfunction, indicating that shunt patency of 1-year post-PS was higher in the patients who received Fluency ® endoprosthesis than those who received Wallgraft ® (87.5% vs 70.0%, P = 0.358)[29]. Another study described the application of PS in 10 cases of cirrhotic patients due to hepatitis B infection[30].…”
Section: Discussionmentioning
confidence: 99%
“…The initial stent position was defined as optimal and suboptimal, with the latter having a higher risk of stent dysfunction. When the cephalic end of the stent does not extend to the hepato-caval junction, the possibility of pseudointimal hyperplasia and thrombosis will be increased, which will ultimately lead to stent dysfunction (17,30,31). Clark et al reported that the initial stent position within the hepatic venous outflow is predictive of shunt patency, with TIPS extension to the hepatocaval junction having a longer lifespan than shunts terminating in the HV (21).…”
Section: Discussionmentioning
confidence: 99%
“…Trans-caval puncture was first described by Haskal et al in 1996 with cases of inaccessible hepatic veins or in cases where the caudal locations of PV bifurcation were close to hepatic veins [3]. In the study of Luo et al on 18 patients, they used the trans-caval approach which was difficult in one patient with Budd-Chiari syndrome [17]. In our study, we performed trans-caval puncture on (33/37) (89.2%) patients with Budd-Chiari syndrome and another one with blocked previous shunt and inaccessible hepatic veins.…”
Section: Discussionmentioning
confidence: 99%